2014
DOI: 10.1371/journal.pone.0107875
|View full text |Cite
|
Sign up to set email alerts
|

The Strong In Vivo Anti-Tumor Effect of the UIC2 Monoclonal Antibody Is the Combined Result of Pgp Inhibition and Antibody Dependent Cell-Mediated Cytotoxicity

Abstract: P-glycoprotein (Pgp) extrudes a large variety of chemotherapeutic drugs from the cells, causing multidrug resistance (MDR). The UIC2 monoclonal antibody recognizes human Pgp and inhibits its drug transport activity. However, this inhibition is partial, since UIC2 binds only to 10–40% of cell surface Pgps, while the rest becomes accessible to this antibody only in the presence of certain substrates or modulators (e.g. cyclosporine A (CsA)). The combined addition of UIC2 and 10 times lower concentrations of CsA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Previous studies have shown that activation of the AKT and ERK1/2 pathways resulted in the resistance to anti-cancer drugs in tumor cells [31, 32]. To determine whether the reversal MDR by ceritinib linked to the blockage of phosphorylation status of AKT and ERK1/2 in K562/adr cells and their parental cells, we examined the total and phosphorylation levels of AKT and ERK1/2 after concentration and time-dependently treating the cells with ceritinib.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that activation of the AKT and ERK1/2 pathways resulted in the resistance to anti-cancer drugs in tumor cells [31, 32]. To determine whether the reversal MDR by ceritinib linked to the blockage of phosphorylation status of AKT and ERK1/2 in K562/adr cells and their parental cells, we examined the total and phosphorylation levels of AKT and ERK1/2 after concentration and time-dependently treating the cells with ceritinib.…”
Section: Resultsmentioning
confidence: 99%
“…demonstrated that UIC2 can inhibit the pumping activity of Pgp and its inhibitory effect is equal to some Pgp inhibitors, such as verapamil, at its highest clinical concentration [ 82 ]. Another study [ 84 ] showed that UIC2 has the ability to bind only to 10–40% of cell surface Pgp, whilst, its ability to bind the rest increases in presence of Pgp substrates or modulators. The investigators found that in vitro combination of UIC2 with Cyclosporine, at ten-fold lower concentration than that used for Pgp inhibition, decreased the EC 50 value of doxorubicin in KBV1 (Pgp+) cells to the same level of KB31 (Pgp−) cells [ 84 ].…”
Section: Pgp or Abcb1 Or Mdr1mentioning
confidence: 99%
“…Another study [ 84 ] showed that UIC2 has the ability to bind only to 10–40% of cell surface Pgp, whilst, its ability to bind the rest increases in presence of Pgp substrates or modulators. The investigators found that in vitro combination of UIC2 with Cyclosporine, at ten-fold lower concentration than that used for Pgp inhibition, decreased the EC 50 value of doxorubicin in KBV1 (Pgp+) cells to the same level of KB31 (Pgp−) cells [ 84 ]. These results were consistent with in vivo studies in immunodeficient mice, which showed a significant decrease in Pgp + tumor weight when treated with a combination of doxorubicin and UIC2 compared with doxorubicin alone [ 84 ].…”
Section: Pgp or Abcb1 Or Mdr1mentioning
confidence: 99%
See 1 more Smart Citation